Problems experienced by older people when opening medicine packaging. (12th September 2013) - Philbert, Daphne; Notenboom, Kim; Bouvy, Marcel L; van Geffen, Erica C G
Abstract: Objective: Medicine packages can cause problems in daily practice, especially among older people. This study aimed to investigate the prevalence of problems experienced by older people when opening medicine packaging and to investigate how patients manage these problems. Methods: A convenience sample of 30 community pharmacies participated in this study. They selected a systematic sample of 30 patients over 65 years old with a recent omeprazole prescription, and a questionnaire was administered by telephone for at least 10 patients per pharmacy. Key findings: A total of 317 patients completed the questionnaire. They received their omeprazole in a bottle ( n = 179, 56.5%), push-through blister pack ( n = 102, 32.2%) or peel-off blister pack ( n = 36, 11.4%). Some 28.4% of all patients experienced one or more problems with opening their omeprazole packaging; most problems occurred with peel-off blisters ( n = 24, 66.7% of all respondents using peel-off blisters), followed by push-through blisters ( n = 34, 33.3%) and finally bottles ( n = 32, 17.9%). The risk of experiencing problems with peel-off blisters and push-through blisters was higher [relative risk 3.7 (95% confidence interval 2.5–5.5) and 1.9 (1.2–2.8), respectively] than the risk of experiencing problems with opening bottles. Two-thirds of respondents reported management strategies for their problems. Most were found for problems opening bottles ( n = 24, 75%), followed by push-through blisters ( n = 24, 70.6%) and peel-off blisters ( n = 14, 58.3%). Conclusions: One in four patients over 65 experienced difficulties opening their omeprazole packaging and not all of them reported a management strategy for their problems. Manufacturers are advised to pay more attention to the user-friendliness of product packaging. In addition, it is important that pharmacy staff clearly instruct patients on how to open their medicine packaging, or assist them in choosing the most appropriate packaging.